Nanoporous Metal Papers for Scalable Hierarchical Electrode - Fujita, Takeshi (Adv Sci (Weinh), 2015)
Nanoporous metals similar to paper in form are developed using Japanese washi paper as a template to create hierarchical porous electrodes. This method is used to create a trimodal nanoporous Au electrode, as a well as a hierarchical NiMn electrode that achieves high electrochemical capacitance and a rapid rate of oxygen evolution. [Image: see text]